Effect of MS-222 on Basal Metabolism of Penaeus indicus Seeds - Das, Chitra; A., Noble (Fishery Technology, 2025)
In laboratory experiments, 150 ppm of MS-222 showed the best effect in delaying the 50 and 100% mortalities respectively to 823 and 1035 min in Penaeus indicus seeds of 15-40 mm sizes as against 293 and 420 min in untreated controls. As a result of the treatment, oxygen consumption was reduced from 0.00859 to 0.00385 ml/mg/h, ammonia excretion from 0.00017 to 0.000022 ppm/mg/h and ammonia quotient from 0.01979 to 0.00571. While carbohydrate and lipid in the tissue of anaesthetised prawns decreased to 0.78 and 3.91% (as is) from 0.82 and 4.08 of non-anaesthetised ones respectively, the protein content increased to 19.28 from 17.21%. The changes in the animals indicate that they were at rest under the influence of the chemical and their death was due to oxygen deficiency developed in the water on account of consumption.